Anxiety levels of Individuals after an Earthquake and Factors Affecting Anxiety Levels: an Elazığ-centered Preliminary Study - Bilici, Rabia; Tufan, Evren; Turhan, Levent; Uğurlu, Görkem Karakaş; Tan, Serap; Kaşan, Turgay (Fırat University, 2013)
Objective: It was aimed to determine sociodemographic characteristics and anxiety complaints of individuals admitted with psychiatric complaints after an earthquake in Elazığ province, and to investigate the factors affecting anxiety levels. Materials and Methods: Individuals who begun to seek psychiatric help following the earthquake and fulfilled the following criteria were included: age >17 years; literacy; and absence of mental retardation or psychotic disorder. A sociodemographic data collection form, the Traumatic Life Events Questionnaire, and the Beck Anxiety Inventory were applied. Results: The mean age of the participants (n=101) was 39.2±17.3 years, and 67.3% of the participants were females. Damage to home and loss of a relative were in question in 55.4% and 12.9% of the participants, respectively. A previous traumatic experience and a history of psychiatric treatment were present in 31.6% and 9.9% of the participants, respectively. The most common previous traumatic events were earthquake/flood and similar natural disasters, with a rate of 27.8%. The mean Beck Anxiety Inventory score was 19.29±12.38. The most common complaint was the fear of something bad happening in the future (73.3%). The mean Beck Anxiety Inventory score was higher in females as compared to males, and in individuals with a previous history of trauma as compared to those without. The frequency of anxiety complaints and relevant scores were higher in females, and in individuals with a history of trauma. Conclusion: Focusing on women and individuals with a previous traumatic experience at the first step after a traumatic event, might enhance the effect of health care provided.

Amaç: Elazığ yöresinde gerçekleşen bir deprem sonrasında psikiyatrik şikayetlerle başvurusu olan bireylerin sosyodemografik özelliklerinin ve anksiyete belirtilerinin ve anksiyete düzeylerine etki eden faktörlerin araştırılması amaçlanmıştır. Gereç ve Yöntem: Depremden sonra psikiyatrik yardım arayışı olanlar arasından okuma yazma bilen, mental retardasyon ya da psikotik bozukluğu olmayan >17 yaş bireyler çalışmaya dahil edildi. Katılımcılara sosyodemografik veri toplama formu, Travmatik Yaşam Olayları Listesi ve Beck Anksiyete Ölçeği uygulandı. Bulgular: Katılımcıların (n=101) ortalama yaşı 39,2±17,3 yıl olup % 67,3'ü kadındı. Katılımcıların %55,4'ünde oturulan evin hasar görmesi ve %12,9'unda depremde yakınlarından birinin kaybı söz konusu idi. Geçmiş travma deneyimi %31,6'sında, geçmiş psikiyatrik tedavi öyküsü ise %9,9'unda bulunmakta idi. Katılımcıların %27,8 oran ile en sık bildirilen geçmiş travmalar deprem/ sel ve benzeri doğal afetlerdi. Beck Anksiyete Ölçeği puan ortalaması 19,29±12,38 olarak saptandı. En sık belirtilen yakınma (%73,3) çok kötü şeyler olacak korkusu idi. Beck Anksiyete Ölçeği puanları kadınlarda erkeklere göre, geçmiş travma öyküsü olanlarda olmayanlara göre yüksekti. Anksiyete belirtilerinin görülme sıklığı ve ilgili puanlar da kadınlarda ve geçmiş travma öyküsü olanlarda yüksek bulundu. Sonuç: Travmatik olaylar sonrasında ilk müdahalede kadınlara ve geçmiş travmaları olan kişilere odaklanılması, yapılan sağlık hizmetlerinin etkisini artırabilir.
Deprem Sonrasında Bireylerin Anksiyete Düzeyleri ve Etkileyen Faktörler: Elazığ Merkezli Bir Ön Çalışma